Biological links between psychological factors and adolescent depression: childhood trauma, rumination, and resilience - Xunyi Guo; Gan Tang; Feng Lin; Haiyan Fang; Jing Chen; Tao Zou (BMC Psychiatry)
Abstract Background The psychosocial factors play an important role in the development of depression in adolescents. we used metabolomics techniques to explore the links among childhood trauma, rumination, resilience, and adolescent depression. Methods We selected 57 adolescent depression patients and 53 healthy adolescents. The Childhood Trauma Questionnaire (CTQ), Hamilton Depression Scale (HAMD), Resilience Scale (CD-RISC), and Redundant Thinking Response Scale (RRS) were employed for the purpose of psychological assessment. The patients were regrouped according to their scores using the 27% high-low grouping method. Blood specimens were collected from all adolescents and metabolic data were obtained using LC–MS. Results We found no statistically significant difference between the groups in terms of age, gender, and body mass index (BMI). HAMD, CTQ, and RRS scores were significantly higher in the adolescent depression group (MDD) than in the adolescent healthy control group (HC), and CD-RISP scores were significantly lower than in the HC group (P < 0.001). There were significant differences between the low childhood trauma group (LCT) and high childhood trauma group (HCT), the low rumination group (LRR) and high rumination group (HRR), and the low resilience group (LPR) and high resilience group (HPR) (P < 0.001). RRS, CTQ and HAMD scores were positively correlated, RRS and CTQ scores were positively correlated, CD-RIS was negatively correlated with HAMD, RRS and CTQ scores (P < 0.01). More importantly, we found that DHEAS and LPA (22:6) were identified as significant differential metabolites in both the depressed and normal groups, as well as in the high and low childhood trauma groups. N-Acetyl-L-aspartic acid and DHEAS were identified as significant differential metabolites in both the depressed and normal groups, as well as in the high and low childhood rumination groups. Pseudouridine and LPA(22:6) were identified as significant differential metabolites in both the depressed and normal groups, as well as in the high and low childhood resilience groups. Conclusion Psychological factors (childhood trauma, rumination, resilience) are biologically linked to the development of depression in adolescents. The impact of rumination on adolescent depression may be associated with DHEA. The impact of childhood trauma and resilience on adolescent depression may be associated with LPA (22:6).